Numerical Analysis on the Performance of the Underwater Excavation - Bo Li; Cangqin Jia; Guihe Wang; Jun Ren; Gaofeng Lu; Nannan Liu (Advances in Civil Engineering, 2020)
Based on the Yongdingmen Station of Beijing Metro, the underwater excavation method for deep foundation pit was introduced. This study constructed a numerical analysis model to analyze the performance of surface settlement and lateral wall deflection in the process of underwater excavation. Results showed that this method was better to control the surface settlement and lateral wall deflection compared with other dewatering excavations. In detail, most of the surface settlement was caused during the dry excavation stage and dewatering excavation stage while the deflection caused by underwater excavation only accounted for about 10% of the total settlement. Besides, the maximum settlement occurred 0.25∼0.5 He behind the retaining wall and the value was 0.04% He. Similar to the result of the surface settlement, most of the lateral wall deflection had been completed before the underwater excavation, which only caused about 7% of the total deflection. The maximum wall deflection and its location were approximately 0.06% He and 0.5 He, respectively. Moreover, a series of 3D numerical analyses were studied on the design parameters of the underwater excavation method. This study can be used as a reference for general performance and structural design of foundation pits with underwater excavation.